Simone Verovio Music printing, intabulations and basso continuo in Rome around 1600 - Campagne, Augusta (2018)
Simone Verovio was the first printer to produce a substantial number of musical prints using engraved copper plates. This intaglio printing technique not only allowed him to print on demand, but also to combine different kinds of notation on one page opening: voice parts with corresponding harpsichord and lute intabulations. This detailed comparison of intaglio and relief printing techniques in the editions associated with Verovio sheds light on the production of sheet music around 1600 and the comparison of the vocal and instrumental parts provides ground-breaking insights into historical performance practice.